The Importance Of Participatory Monitoring In Guarding Democratic Elections - Ayub Fahmi; Melia Wida Rahmayani (GAYAKU PUBLISHER, 2022)
Stakeholders (stakeholders) and the community are independently involved in overseeing the implementation of general elections (PEMILU). This paper examines the importance of participatory supervision in overseeing the implementation of elections, which aims to create democratic elections. The method used in this study is a qualitative approach through literature studies. This paper discusses the problems that arise in the context of participatory supervision in the implementation of general elections (PEMILU). General election activities (PEMILU) carry out participatory supervision that has been carried out by election monitoring institutions and other civil society organizations and various efforts have been made in participatory supervision to oversee democratic general elections in accordance with applicable laws and regulations in Indonesia.